Functionality multiplexing in high-efficiency metasurfaces based on coherent wave interferences - Yuejiao Zhou; Tong Liu; Changhong Dai; Dongyi Wang; Lei Zhou (Opto-Electronic Advances)
Multiplexing multiple yet distinct functionalities in one single device is highly desired for modern integration optics, but conventional devices are usually of bulky sizes and/or low efficiencies. While recently proposed metasurfaces can be ultra-thin and highly efficient, functionalities multiplexed by metadevices so far are typically restricted to two, dictated by the number of independent polarization states of the incident light. Here, we propose a generic approach to design metadevices exhibiting wave-control functionalities far exceeding two, based on coherent wave interferences continuously tuned by varying the incident polarization. After designing a series of building-block metaatoms with optical properties experimentally characterized, we construct two metadevices based on the proposed strategy and experimentally demonstrate their polarization-tuned multifunctionalities at the wavelength of 1550 nm. Specifically, upon continuously modulating the incident polarization along different paths on the Poincare’s sphere, we show that the first device can generate two spatially non-overlapping vortex beams with strengths continuously tuned, while the second device can generate a vectorial vortex beam carrying continuously-tuned polarization distribution and/or orbital angular momentum. Our proposed strategy significantly expands the wave-control functionalities equipped with a single optical device, which may stimulate numerous applications in integration optics.